Studi Pustaka Sistematis: Mahabah dalam Tasawuf Kontemporer Perspektif Buya Nursamad Kamba - Hidayatul Fikra (Fakultas Ushuluddin UIN Sunan Gunung Djati Bandung, 2021)
Mahabah which is the peak of sufism becomes a proper study considering that contemporary life today often makes sense more than the real God. The purpose of this study is to explore how the reflection of the mahabah when viewed from the perspective of a contemporary sufi, Buya Nursamad Kamba. The research method used is descriptive-qualitative with a library research approach. The results showed that the point of view taken by Buya Nursamad Kamba in perceiving mahabah is by focusing on the concept of Muhammad’s personality by elaborating and integrating the value of love for Allah in every aspect of life. The conclusion that can be drawn from the results of this study is Buya Nursamad Kamba's view of the concept of mahabah is very unique and adapts to the development of the times in this contemporary era.